Toxoplasma gondii AND Rotavirus ASSOCIATED WITH CAMEL-CALF DIARRHEA IN SUDAN - Ishag, M.Y.; Ali, Y. H.; Majid, A.M . (Journal of Veterinary Medicine and Animal Production, 2021)
The aim of this study was to determine the role of Toxolasma gondii and rotavirus infection in camel-calves diarrhea in Sudan. Toxoplasma gondii and Rotavirus are considered as causative agents of calf-diarrhea. 278 serum samples were collected from diarrheic camel-calf (less than one year age) in five locations in Sudan ; River Nile(North), El-Gedarif (East), Sennar &Blue Nile (Central to South) and kordofan (West). Out of 278 serum samples,157 sera (56.5%) were sero-positive for anti-Toxoplasma antibodies by latex agglutination test, ELISA test was applied on the sero-reacted sera, IgM and IgG were detected in sera. Also a competitive ELISA kits for rotavirus antibodies detection were used , results showed that 66 sera ( 23.7%) were sero-positive for rotavirus antibodies . Statistical analysis using software analysis programs showed no significant difference (P>.05) between the five surveyed locations for both Toxoplasma and rotavirus infections. The sero-prevalence of rotavirus in different age groups was found to be statistically significant (P<.05), however, there is no statistical difference in the occurrence of Toxoplasma in different age groups ; this may reveal an occurrence of congenital infection. There was no statistical difference (P >.05) in the occurrence of sero-prevalence of Toxoplasma and rotavirus in males and females.